Food security in South Asia under climate change and economic policies. Issue 3 (27th April 2022) - Yan, Sun; Alvi, Shahzad
Abstract : Purpose: The first purpose of this study is to examine the impacts of climate-caused cereal productivity changes on food security, welfare and GDP in South Asian countries. The second purpose is to assess the agricultural subsidies and South Asia Free Trade Agreement (SAFTA) as policy responses to climate change. Design/methodology/approach: The present study uses the computable general equilibrium (CGE) framework and econometric approach in an integrated manner to examine the economic impacts of climate-caused cereal productivity changes in South Asian countries. An econometric model is used to identify the impact of climate change on cereal yields and CGE approach is used to assess the future effect of climate change through simulations. In this course, the econometric findings are applied to Multiregional Global Trade Analysis Project 10 and then the model is calibrated for future projection. Findings: The results indicate that there is a decrease in cereals production because of climate change and eventually it increases the prices of cereals, decreases the local consumption and GDP and, as a result, causes a loss in welfare. Subsidies and SAFTA have been found to have no substantial impact on increasing food security in South Asia. Originality/value: The present study uses the concept of food demand for all cereals in an integrated way and focuses on the fiscal and trade policy responses to climate change.